2020
DOI: 10.1002/ep.13512
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the energetic potential of Mediterranean food waste by anaerobic co‐digestion with sewage sludge

Abstract: Mediterranean Food Waste (FW) with high Carbon/Nitrogen (C/N) ratio (≈31) and a biodegradability (BD) above 75%, were anaerobically co‐digested with Sewage Sludge (SS), in both batch and semicontinuous processing systems. Biochemical Methane Potential (BMP) tests were carried out for five mixture ratios (VS basis). The highest methane yield was obtained for the Food Waste to Sewage Sludge (FW/SS) ratio of 3:1, reaching a Specific Methane Production (SMP) of of 452 ml CH4/g VSadded. Moreover, this ratio has sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…As far as the 3/1 ratio is concerned (447 ml/g VS), [39] research reported a lower speci c production of 246 ml/g VS, which might be explained by SARS-CoV 2 presence in the feed. In studies [40] and [41] whose results are in opposite areas of very unlikely observations (with productions of 175 and 744 ml/g VS, respectively), no additions were made.…”
Section: Resultsmentioning
confidence: 98%
“…As far as the 3/1 ratio is concerned (447 ml/g VS), [39] research reported a lower speci c production of 246 ml/g VS, which might be explained by SARS-CoV 2 presence in the feed. In studies [40] and [41] whose results are in opposite areas of very unlikely observations (with productions of 175 and 744 ml/g VS, respectively), no additions were made.…”
Section: Resultsmentioning
confidence: 98%
“…In another study on the AcoD of FVW with the SS, the measured CMP was 119 mL/gVS in the monodigestion of primary sludge [ 21 ]. Similarly, the CMPs were determined to be 133 and 190 mL/gVS for SS consisting of primary sludge and waste-activated sludge in studies performed to determine a suitable mixing ratio for the AcoD of SS with food waste [ 22 , 31 ]. The values for the CMP of SS reported in the above-mentioned studies are quite similar to the CMPs obtained in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…In the AcoD, it is very important to determine the most suitable cosubstrates and mixing ratio to maximize methane production with a synergistic effect and prevent the production of inhibitory components that can cause an antagonistic effect [ 17 , 19 ]. Sewage sludge, known to have a high nitrogen content, has been preferred as a cosubstrate to provide the optimum C/N ratio in the anaerobic digestion of agricultural wastes with a high carbon content [ 20 , 21 , 22 ]. Codigestion of agricultural wastes with sewage sludge (SS) can increase biogas production by (i) maintaining an optimal pH for bacteria, (ii) decreasing free ammonia/ammonium inhibition and (iii) providing a better C/N ratio during anaerobic digestion [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Assuming an average collection and transportation distance of 100 km, then each ton of kitchen waste collection and transportation process would require 4 L of diesel. At a diesel density of 0.84 g/cm 3 , the diesel consumption for this transportation process was ~3.36 kg. (2) Production of biogas through pretreatment and co-digestion processes: The processing scale was 150 t/day.…”
Section: Environmental Impact Assessment Of Anaerobic Co-digestion Of...mentioning
confidence: 99%
“…Anaerobic co-digestion treatment technology refers to the method of anaerobic digestion treatment of two or more organic wastes at the same time according to the characteristics of different biomass wastes. Several studies have examined the anaerobic co-digestion of kitchen waste and residual sludge to balance the nutrient ratio of the substrate [2], which results in complementary effects and improves gas production efficiency [3,4]. Pan Y et al investigated the synergistic effect and biodegradation kinetics of residual sludge and kitchen waste in the anaerobic co-digestion process.…”
Section: Introductionmentioning
confidence: 99%